Effect of Time in the Synthesis of an Intermediate of Phenothiazine Derivatives - Feng, Xiao-Jun; Dong, Hua-Ze (Asian Journal of Chemistry, 2010)
During the synthesis of a derivative from phenothiazine, two distinct competitive reactions were detected. In this paper, some proofs about these reactions were examined.